Sosialisasi Hak Kekayaan Intelektual untuk Produk Unggulan Desa Puuroda - ⁠Ninis Karlina; Nur Afni Pertiwi; Ridah Astuti; Afliani Afliani; Febrina Anggraini Hijriah; Jeis Mawar M; Sumardianto Sumardianto; Nova Yovianti; Sumardin Sumardin; Nurul Adha; Johar Nur Iin; Faisal Herisetiawan Jafar (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
ABSTRACT Fertile soil makes Puuroda village one of the food barn centers of Kolaka district with superior products of organic rice cap Anoa, besides that there is an organic study center managed by the Organic Farmers Association (ASPOK) of Puuroda village with exceptional products such as Jamu busset, flower telang tea by indah, rosela flower fresh drinks, rengginang mentik Susu (Remensu). However, the superior products in the village do not yet have an Intellectual Property Rights (IPR) certificate registered with the Directorate General of Intellectual Property. This community service aims to socialize intellectual property rights for superior products in Purooda village. The results of this community service activity are an understanding of the IPR category, brand naming, brands that cannot be registered, brand registration functions, protection of brands, registration flow, brand registration fees, and examples of IPR brands that have been registered. This community service is expected to help the Puuroda village community to increase awareness of the importance of intellectual property rights in encouraging innovation in the village, so that these innovations can have a maximum impact on society.